Short-term Labour Migration from the Republic of Armenia to the Russian Federation: Empirical Study on Determinants and Effects. - Bellak, Christian; Leibrecht, Markus; Liebensteiner, Mario (Journal of Development Studies, 2014)
We explore the determinants of short-term labour migration from Armenia to Russia based on a unique panel dataset. A dynamic switching regression model with endogenous switching is applied. Our evidence pinpoints migration experience, the expected individual income gap from migration, low job opportunities in Armenia and the possibility of diversifying income risks as the most important determinants. Family ties turn out to be insignificant. The hypothetical income gap is about 280 per cent. Several explanations are provided for the fact that some individuals do not migrate in spite of a large income ga